KARAKTERISTIK HABITAT IKAN CUPANG LIAR (WILD BETTA) ENDEMIK SEBAGAI DASAR PENGEMBANGAN POTENSI BUDIDAYA DI KABUPATEN LABUHANBATU RAYA - Rifai, Ahmad; Khairul, Khairul; Dimenta, Rivo Hasper; Siregar, Zunaidy Abdullah (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2023)
Wild betta fish has high economic value as one of the ornamental fish commodities in Indonesia.  The potential for cultivation development so far has not been maximized so that it still relies on the results of capture from nature. The main key to the development of wild fish farming is actually dependent on food conversion and water quality. Water quality management must adjust to its habitat in nature, however, the study of the physical chemical parameters of wild betta fish waters endemic to Sumatra has not been widely reported. Studies related to habitat characteristics can be used as the basis for aquaculture management in the future. This study aims to analyze the condition of the physical parameters of aquatic chemistry in the natural habitat of wild betta fish in the Regency Labuhanbatu Selatan, Labuhanbatu, and Labuhanbatu Utara. This research is exlorative by observing physical and chemical factors carried out insitu and exitu. The research data is analyzed quantitatively, presented discriptively and discussed based on relevant literature. The results of the main component analysis (Principal Component Analysis) show the main characteristic parameters of wild betta fish habitat in the form of: BOD, COD, DO, conductivity, temperature, and pH. Based on the results of UPGMA analysis, the percentage of similarity of stations 1 and 2 (90.5%) while station 3 (83.6%). It was concluded that the key parameters for wild betta fish farming activities are BOD, COD, DO, conductivity, temperature, and pH and these parameters need to be measured continuously.